Magnetic resonance imaging in monitoring the treatment of multiple sclerosis: concerted action guidelines. - Miller, D H (1991)
Serial gadolinium enhanced MRI of the brain detects much clinically silent disease activity in early relapsing-remitting and secondary progressive multiple sclerosis (MS), and thus has an important role in monitoring the effects of therapy. Based on the proceedings of a recent Commission of the European Communities (CEC) workshop and a review of the literature, guidelines are presented for using MRI to monitor treatment trials in MS. The guidelines consider: A) MRI system and techniques; B) patient selection; C) trial design; D) analysis of results. Priorities for future research are also indicated.